KONTRIBUSI GURU BIMBINGAN DAN KONSELNG DALAM PEMBELAJARAN JARAK JAUH - Ronald Haries Hamonangan (Jurnal Ilmu Pendidikan dan Sosial, 2022)
The purpose of this study was to analyze and determine the contribution of guidance and counseling teachers to distance learning as well as to analyze and determine the supporting and inhibiting factors of teachers in providing guidance and counseling services to students. The research method used is a qualitative research method with a descriptive approach, namely by collecting data as it is from a symptom of a phenomenon that existed when the research was conducted. The data and data sources used were guidance and counseling teachers and class IX students who were taken based on a purposive sampling of 40 people. The research instruments used in this study were questionnaires, interviews and observations. Questionnaires were conducted by 40 students in class IX, interviews were conducted with guidance and counseling teachers as well as students in class VIII and observations were made by observing the state of the school environment and the existence of the school. Data analysis techniques are carried out by collecting data, managing data, analyzing data and interpreting the data to be concluded. The conclusion of this study is that the role of guidance and counseling teachers in overcoming students' learning anxiety in distance learning is in the Good category.